Impact Assessment of Violent Conflict and Internal Displacement on Housing and Shelter in the Northern Senatorial Zone of Plateau State - Dingba, Abigail Benedict; Plang , Janet Punyit; Wika, Peter Nunshak (Kashere Journal of Politics and International Relations, 2025)
The housing crisis affecting displaced persons and the need for a holistic strategy to achieve durable solutions necessitated this study. The study examines the impact of violent conflict and internal displacement on housing and shelter conditions in the Northern Senatorial Zone of Plateau State, Nigeria. Violent conflict has been a primary driver of internal displacement in the region, leading to significant loss of life and disrupting the socioeconomic fabric of affected communities. Utilizing a mixed-methods approach, the quantitative component involved surveying 380 households selected from a total population of 37,665 internally displaced households across the Local Government Areas of Barkin Ladi, Bassa, and Riyom. A purposive sampling was further used to administer interviews to 9 key informant respondents and 10 in- depth interviewees. Human needs theory was used as a framework of analysis. Findings from the quantitative analysis indicate substantial housing destruction, inadequate shelter provision, and increased exposure to precarious living conditions. These results are reflected in the qualitative data, where respondents reported widespread demolition of homes and displacement to less secure environments, along with inadequate financial support for housing reconstruction. Additionally, the study found that mass migration has contributed to the desolation of several affected villages. The study calls for stringent government intervention, including proactive measures to mitigate community conflict and address external factors that exacerbate these crises.